2014
DOI: 10.3171/2014.7.gks141272
|View full text |Cite
|
Sign up to set email alerts
|

Calvarial and skull base metastases: expanding the clinical utility of Gamma Knife surgery

Abstract: ObjectTraditionally, the treatment of choice for patients with metastases to the calvaria or skull base has been conventional radiation therapy. Because patients with systemic malignancies are also at risk for intracranial metastases, the utility of Gamma Knife surgery (GKS) for these patients has been explored to reduce excess radiation exposure to the perilesional brain parenchyma. The purpose of this study was to report the efficacy of GKS for the treatment of calvarial metastases and skull base lesions.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…The treatment of choice was 3D conformal RT with conventional fractionation (2 Gy per fraction) up to 55 Gy (3,29). Clinical experience with other RT techniques, such as stereotactic RT, was only limited to a retrospective analysis of 14 calvarial bone lesions (33). A 201-source 60Cobalt gamma knife radiosurgery system was used.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of choice was 3D conformal RT with conventional fractionation (2 Gy per fraction) up to 55 Gy (3,29). Clinical experience with other RT techniques, such as stereotactic RT, was only limited to a retrospective analysis of 14 calvarial bone lesions (33). A 201-source 60Cobalt gamma knife radiosurgery system was used.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent complications are pathological fractures and compression of the spinal cord 15. Management of these metastases can often be complex and demands a multidisciplinary approach: analgaesic, surgical and radiotherapy treatment 11. In many patients, current treatment is palliative and not curative.…”
Section: Discussionmentioning
confidence: 99%
“…Only 0.2% of intracranial tumors found in the CPA are metastatic in origin. 1 10 RCCs have an 11% incidence of brain metastases representing ∼ 1,100 patients per year. 11 A literature search revealed nine case reports of metastatic RCC presenting within the skull base and five case reports presenting within the sinonasal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the relative radioresistance of RCC to traditional fractionated radiation delivery, radiation therapy and/or radiosurgery in combination with resection and systemic chemotherapy are the current treatment algorithms. 3 10 11 18 19 20 Shuto et al demonstrated the effectiveness of GKS with a dose ≥ 20 Gy for the treatment of metastatic brain tumors from RCC < 3 cm in maximum diameter. 21 Additionally, adjuvant chemotherapeutic drugs targeting tyrosine kinase receptors such as sorafenib and sunitinib show promise as second-line agents for the treatment of metastatic RCC.…”
Section: Discussionmentioning
confidence: 99%